It's not “either/or”: activation and desensitization of nicotinic acetylcholine receptors both contribute to behaviors related to nicotine addiction and mood - Picciotto, Marina R. (2007)
Nicotine can both activate and desensitize/inactivate nicotinic acetylcholine receptors (nAChRs). An ongoing controversy in the field is to what extent the behavioral effects of nicotine result from activation of nAChRs, and to what extent receptor desensitization is involved in these behavioral processes. Recent electrophysiological studies have shown that both nAChR activation and desensitization contribute to the effects of nicotine in the brain, and these experiments have provided cellular mechanisms that could underlie the contribution of both of these processes to nicotine-mediated behaviors. For instance, desensitization of nAChRs may contribute to the salience of environmental cues associated with smoking behavior and activation and desensitization of nAChRs may contribute to both primary and conditioned drug reward. Similarly, studies of the antidepressant-like effects of nicotinic agents have revealed a balance between activation and desensitization of nAChRs. This review will examine the evidence for the contribution of these two very different consequences of nicotine administration to behaviors related to nicotine addiction, including processes related to drug reinforcement and affective modulation. We conclude that there are effects of nAChR activation and desensitization on drug reinforcement and affective behavior, and that both processes are important in the behavioral consequences of nicotine in tobacco smoking.